LANDASAN EPISTEMOLOGIS ILMU BAIK DALAM PERSPEKTIF BARAT DAN ISLAM - Ihsan, Ihsan; Saputra, Riki; Saifullah, Saifullah (Ensiklopedia of Journal, 2025)
Epistemology, as a major branch of philosophy, explores the sources, methods, and validity of knowledge. This study compares the epistemological foundations of science from Western and Islamic perspectives to identify differences in paradigms and potential synergies between the two. In the Western tradition, epistemology tends to be anthropocentric, prioritizing rationalism and empiricism as sources of knowledge. In contrast, the Islamic tradition integrates revelation, reason, and the senses in a theocentric framework, with the main goal of bringing humans closer to Allah. This study uses a descriptive-comparative qualitative approach, with literature analysis from various relevant sources. The research results show that Islamic epistemology offers a comprehensive approach that is able to complement modern Western scientific methods. In the context of globalization, synergy between the two paradigms can enrich scientific understanding while maintaining spiritual identity and Islamic values. This article recommends the development of an integrative approach to address contemporary challenges and build a more just and balanced civilization.Keywords: Epistemology, Philosophy of Science, Western Perspective, Islamic Perspective, Integrative Approach